STORYTELLING-BASED EDUCATION IN DIABETIC FOOT CARE: A SYSTEMATIC REVIEW OF SELF-EFFICACY AND RISK - Anih Kurnia; Betty Suprapti; Teti Agustin; Jabarul Ikrom Rahmantara; Rochmanah Suhartati (Universitas Airlangga, 2026)
Introduction: Diabetic Foot Ulcer (DFU) is a serious complication of Type 2 Diabetes. It is often caused by poor self-management and low health literacy. Traditional education often fails to change patient behavior because it lacks emotional engagement. Storytelling offers a narrative approach to address this issue. It can improve understanding and increase patient involvement in their own care. This systematic review evaluates the effectiveness of storytelling and narrative-based interventions for individuals with T2DM. It specifically focuses on improving self-efficacy, risk perception, and foot-care behaviors to prevent diabetic foot ulcers. Methods: This systematic review followed the PRISMA 2020 guidelines. Searches were conducted in PubMed, CINAHL, Web of Science, and Google Scholar for studies published between 2024 and 2026. Ten studies, including randomized controlled trials and mixed-methods designs, met the inclusion criteria. Data were extracted systematically and synthesized thematically. Results: Storytelling interventions—including digital narratives, AI-assisted media, and culturally adapted tools—consistently outperformed conventional education. Findings show significant improvements in self-efficacy, motivation, and foot-care adherence. Some studies also reported better glycemic control. Key mechanisms for behavioral change included emotional engagement with characters and the internalization of health risks. Conclusions: Storytelling is a superior educational strategy for DFU prevention compared to traditional methods. Integrating culturally adapted narratives into community nursing can enhance patient empowerment and long-term self-management. This approach effectively strengthens patient engagement and supports lasting behavioral change.